City Morphology and Women’s Perception of Travel: A Case Study for Istanbul, Turkey - Khorsheed, J. (CRC Press, 2020)
Where gaps exist between urban design practices and urban transport planning, problems are cre-ated for travellers, especially for vulnerable groups of travellers such as women. These gaps evolve particularly when in urban design the focus is only on the physical structures involved, thereby ignoring social needs and those of individuals in design and planning. As such, mobility behaviours and preferences are also ignored. To tackle this issue, we developed a theoretical framework that addresses the city’s physical and social elements with respect to the travel behaviour of women. Aided by participatory GIS, the framework we describe in this chapter combines and links various theories from urban design, urban morphology, transport planning and the behavioural sciences (focusing on gender-sensitive perceptions). These various dimensions are applied in a case study of several neighbourhoods in Istanbul, Turkey.